FACTORS OF THE FORMATION OF ECONOMIC SECURITY OF MANUFACTURING BUSINESSES IN TOURIST AREA - Loyak, L. M. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The subject of the research is theoretical and methodological basis of economic security in manufacturing businesses formation. The purpose of the study is to research the factors of the ways how to ensure economic security of manufacturing businesses in tourist area. Methods of the research. There is a set of scientific methods and approaches used in the study, including logical synthesis, systematic method of comparison and graphic method, allowing for conceptual coherence. The results of the work. The need for formation of economic security in manufacturing businesses in tourist industry under the condition that the sustainability of operating and development processes is achieved, is justified the article. The sphere of application of the results. In the industry of Economic Science and in practical manufacturing businesses activities. Conclusions. Main outcomes of the research and its theoretical and methodological results can be summarized as the following wording: based on an assessment of condition of food industry as strategically important sphere, that provides economic well-being of the population of the region and effective development of tourism, which is unstable and depends on the impact of different factors (the degree of legislative framework perfection, level of taxation, global distribution market access, investment attractiveness of the region and state), updates the need for study and research of new and improvement of already known methods of safety net ensuring. In order to achieve the highest possible level of economic security, enterprise has to work for retention in security of all its functional components, complex study of the impact of different factors that create threats to its stable development and effective functioning. However, we should take into account that the economic and legal institutional arrangements which form the basis of security system, are significant for economic security.